Father's Role in Shaping Character of Responsibility in Early Childhood - Rustiana, R; Asmawulan, Tri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The role of fathers in early childhood care plays an important role in character formation, including the character of responsibility. This study aims to examine how father's involvement affects the development of responsibility character in early childhood. Methodology: Although there have been many studies that have discussed the important role of fathers in parenting, previous studies have often focused on general aspects of fathers' involvement without delving into specific contexts, such as the type of work or family structure. Some studies also tend to emphasize quantitative engagement (how often dads are present) without looking at the quality of the interactions made. The subjects of this study are children with fathers who have different parenting involvements, where some fathers have limited time in parenting. Data were collected through interviews and observations of children and their fathers, using a qualitative approach. The data analysis technique used is thematic analysis to identify patterns of fatherly involvement and its impact on the formation of responsibility character. Results: The results of the study show that limited involvement of fathers, both due to busy work and family conditions, has a negative impact on the formation of children's responsible character. Applications/Originality/Value: The results of the study show that limited involvement of fathers, both due to busy work and family conditions, has a negative impact on the formation of children's responsible character.